Flood Identification Using Google Earth Engine and Correlation with Disaster Risk Level in Tanjungpinang City - Dewi, Dian Kharisma; Zulfakar, Muhamad; Sukmawan, Muhammad Fatwa; Oktavia, Ferly (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2025)
Tanjung Pinang, the capital city of Kepulauan Riau Province, experienced a significant flood in early January 2021. The rainfall intensity during this event reached approximately 282.6 mm/hour, the highest recorded since 2011. This flood caused extensive damage to several facilities and residential areas. The impact of such disasters can be mitigated through identification, evaluation, and preventive measures. One such preventive approach is flood identification, which involves mapping flood extent areas. This study utilized Google Earth Engine (GEE), a web-based application platform, to achieve this. The advanced capabilities of GEE enabled the identification of flood distribution in January 2021. The results revealed that the cumulative flood distribution area was 37.89 hectares on January 2 and 149.88 hectares on January 10, with the largest affected area in Tanjungpinang Timur, covering 89.858 hectares. Based on the disaster risk level guidelines outlined in Regulation Number 02/2012, issued by BNPB, the floods on January 2 and 10, 2021, were classified as ‘High-Level’ disasters.